Towards entrepreneurship education: Empowering township members to take ownership of the township economy - Manyaka-Boshielo, Semape J. (HTS teologiese studies, 2019)
This article explores the role of effective entrepreneurial education in township communities, to address some of the economic challenges facing poor township communities. Effective entrepreneurial education has the potential to ignite economic transformation in township communities. This effective entrepreneurial enterprise should be based on the understanding of whole education principles. This article also explores the role of the social missional entrepreneurial church by applying effective enterprises that would run entrepreneurial activities in township communities. The social missional entrepreneurial church understands that it should approach its mission holistically; ‘holistic’ here referring to the spiritual, physical, mental, social, emotional and economic spheres. This explorative study aims at understanding how to implement the social missional entrepreneurial enterprises in township communities. It explores effective entrepreneurial programmes that could be an engine in transforming the township communities. It focuses on the definition of education, specifically entrepreneurship education, and how can it be implemented effectively. This entrepreneurship education should resonate with those who live in township communities. It should address the needs and challenges that face township communities. The article will also explore the meaning of the township economy. It will examine the role of Churchpreneur, which refers to the social missional entrepreneurial church in the spotlight, and how this kind of church can be a place where entrepreneurial education is promoted.